Is Undernutrition Associated With Deterioration of Outcomes in the Pediatric Intensive Care Unit (PICU): Systematic and Meta-Analysis Review - Albadi, Maram S.; Bookari, Khlood (Frontiers in Pediatrics, 2022)
Background and Aim: Undernutrition may negatively impact clinical outcomes for hospitalized patients. The relationship between UN status at pediatric intensive care unit (PICU) admission and clinical outcomes is still not well-reported. This systematic meta-analysis review evaluated the impact of UN at admission to PICU on clinical outcomes including mortality incidence, length of stay (LOS) and the need for and length of time on mechanical ventilation (MV). Methods: A search was conducted using relevant and multi-medical databases from inception until January 2022. We considered studies that examined the link between undernutrition at PICU admission and clinical outcomes in patients aged 18 years or younger. Pooled risk difference estimates for the PICU outcomes were calculated using a random effects model. Result: There was a total of 10,638 patients included in 17 observational studies. 8044 (75.61%) and 2594 (24.38%) patients, respectively, were normal-nourished (NN) and undernourished (UN). In comparison to NN patients, UN patients had a slightly higher risk of mortality (RD= 0.05, P= 0.0005), MV usage, and PICU LOS by 7% (RD 0.07, P= 0.05). While the duration of MV was significantly longer in UN than in NN (RD 0.13, P= 0.0001). Sensitivity analysis of undernutrition classification cohorts with a <-2 z-score or in the 5% demonstrated a sixfold increase in the probability of using MV and PICU LOS in UN patients compared to NN patients. UN patients have a longer LOS in the PICU (RD 0.08, 95% CI 0.02, 0.13) and a higher risk of MV usage (RD 0.12, 95% CI 0.02, 0.21) in studies that conducted in developing countries and involving cohorts with a specific primary diagnosis for PICU admission. Conclusion: In PICU, UN is linked to higher PICU stay, MV use, and duration on MV. The primary diagnosis for PICU admission may also influence clinical outcomes. Determining the prevalence of undernutrition in hospitalized patients, as well as the subgroups of patients diagnosed at the time of admission, requires more research. This may help explain the relationship between nutritional status and clinical outcomes in PICU patients.